Porter Anderson meets Peter Meyers. (Bookseller, 2014)
The article presents the interview of writer Peter Meyers by journalist in publishing Porter Anderson via tweets or posts in microblogging site Twitter. Topics discussed include the new book of Meyers titled "Breaking the Page: Transforming Books and the Reading Experience," the digital print trend, and the many kinds of reading. Also examined are the part of books with a network digital culture, and the importance of software development.